Introduction to messianic Judaism : its ecclesial context and Biblical foundations - Rudolph, David J.; Willitts, Joel. (Grand Rapids, MI : Zondervan, 2013)
Editors David Rudolph and Joel Willitts have assembled a thorough examination of the ecclesial context and biblical foundations of the diverse Messianic Jewish movement. This book uniquely brings together a team of respected Messianic Jewish and Gentile Christian scholars, including Mark Kinzer, Richard Bauckham, Markus Bockmuehi, Craig Keener, Darrell Bock, Scott Hafemann, Daniel Harrington, R. Kendall Soulen, Douglas Harink, and others. Opening essays, written by Messianic Jewish scholars and synagogue leaders, provide a window into the on-the-ground challenges and questions with which Messianic Jews grapple. The following predominantly Gentile Christian discussion explores a number of biblical and theological issues that inform our understanding of Messianic Judaism. -- BOOK COVER
Messianic Judaism in antiquity and in the modern era / David Rudolph -- Messianic Jewish synagogues / David Rudolph and Elliot Klayman -- Messianic Jewish worship and prayer / Seth N. Klayman -- Messianic Jews and Scripture / Carl Kinbar -- Messianic Jews and Jewish tradition / Carl Kinbar -- Messianic Jewish ethics / Russ Resnik -- Messianic Jewish outreach / Stuart Dauermann -- Messianic Judaism and women / Rachel Wolf -- Messianic Jews in the Land of Israel / Akiva Cohen -- Messianic Jewish national organizations / Mitch Glaser -- Messianic Jews in the Jewish world / Mark S. Kinzer -- Messianic Jews and the Gentile Christian world / Daniel C. Juster -- Messianic Jews and Jewish-Christian dialogue / Jennifer M. Rosner -- Matthew's Christian-Jewish community / Daniel J. Harrington -- The restoration of Israel in Luke-Acts / Darrell Bock -- James and the Jerusalem Council decision / Richard Bauckham -- Interdependence and mutual blessing in the church / Craig Keener -- The relationship between Israel and the church / William S. Campbell -- The redemption of Israel for the sake of the Gentiles / Scott J. Hafemann -- Paul's rule in all the Ekklesiai / Anders Runesson -- Equality in the church / Justin K. Hardin -- The supersession and superfluity of the law? Another look at Galatians / Todd A. Wilson -- The bride of Messiah and the Israel-ness of the new heavens and new earth / Joel Willitts -- Mission-commitment in Second Temple Judaism and the New Testament / John Dickson -- The son of David and the Gospel / Markus Bockmuehl -- Jewish priority, election, and the Gospel / Douglas Harink -- The standard canonical narrative and the problem of supersessionism / R. Kendall Soulen.
Includes bibliographical references and index.
Keywords: Messianic Judaism